Role of the fusogenic peptide sequence in syncytium induction and infectivity of human immunodeficiency virus type 2. - Steffy, K R (1992)
Syncytium induction is a characteristic feature of infection by human immunodeficiency virus (HIV) in vitro. The hydrophobic amino terminus of the transmembrane glycoprotein of HIV type 1 is an essential determinant of virus entry into the target cell population and the formation of syncytia in cell culture. To define the role of the HIV type 2 fusion peptide during infection and syncytium formation, we introduced 8 amino acid substitutions into the hydrophobic amino terminus of gp41, changing either the hydrophobicity, the charge, or the polarity of the amino acid. Viruses containing the envelope mutations were analyzed for their syncytium-inducing capacities, levels of infectivity, and envelope processing and expression. Mutations that increased the hydrophobic nature of the fusion peptide increased syncytium formation, whereas mutations which increased the charge and the polarity and/or decreased the hydrophobicity of the fusion domain severely reduced the capacity of the virus to induce syncytia. However, viruses severely compromised for syncytium formation exhibit only slightly lower levels of infectivity.